The international legal obligation to fight against corruption and its compliance within the Spanish State - Capdeferro Villagrasa, Oscar (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
In the light of the International law, to fight against corruption can be understood as compulsory for the States, since some treaties containing specific obligations in this regard have been adopted. In this article, the main international treaties ratified by Spain imposing –through their incorporation in the domestic law ex art. 96.1 SC– the adoption of preventive and sanctioning measures are analysed. The formal analysis of the international instruments and their implementation mechanisms allows us to identify the characteristics of the assumed obligations and the observed implementation degree in Spain, what could be used to guide future legal reforms.